Growth and carcass composition of tropical fat-tailed Menz and Horro sheep breeds - Eneyew, N.; Rottmann, O.J.; Pirchner, F.; Rege, J.E.O. (2004)
The pattern of growth and carcass composition of indigenous Ethiopian fat tailed Menz and Horro lambs were assessed through serial slaughter and carcass dissection of 147 lambs at five different growth phases. The GLM procedure of Statistical Analysis Systems Institute and allometric growth equations were used to assess the effect of various factors and differential growth of carcass components, respectively. Results showed that the growth and carcass composition of Menz and Horro lambs was significantly (P < 0.05 to P < 0.001) affected by the genotype growth phase and season of birth of lambs. The effects of growth phase clearly showed that slower growth of the body and of carcass components was observed during the third phase (i.e. after weaning). Although there was an effect on fat to lean ratios (P < 0.05), growth phase had no significant effect on dressing out proportion, and lean to bon ratios. A significant influence of genotype (P < 0.001) and sex (P < 0.05) on lean to bone ratios indicated that the Horro sheep and ram lambs had a much more developed and heavier skeleton than the Menz sheep and ewe lambs Higher pre slaughter, hot carcass, lean and bone and fat weights of May/June born lambs revealed significant advantages of wet season lambing for fast growth and improved carcass composition. The log/log regression of weights of dissectible carcass components on hot carcass and empty body weight showed that the differential growth of bone was declining and that of lean was isometric relative to the growth of empty body weight. For carcass fat, the allometric growth coefficients (b) of 1.5 and 1.8 for Menz and Horro sheep, respectively indicated that fat is a late maturing body component. Moreover the growth of carcass fat relative to empty body weight in the Menz and Horro sheep is slower than that reported for tropical sheep breeds.